Efficacy of reduced rate fumigant alternatives and methyl bromide against soilborne pathogens and weeds in western forest nurseries. (July 2016) - Weiland, Jerry E.; Littke, Willis R.; Browning, John E.; Edmonds, Robert L.; Davis, Anne; Beck, Bryan R.; Miller, Timothy W.
Abstract: Preplant soil fumigation is commonly used to control soilborne pathogens and weeds in forest seedling nurseries of Oregon and Washington. However, lower chemical inputs are desired to meet state and federal application regulations, to minimize buffer zone size requirements, and to help protect the environment. Therefore, the objectives of this research were to evaluate the efficacy of three reduced rate soil fumigants under totally impermeable film (TIF) in managing soilborne diseases and weeds, and to determine if combined applications of up to four biocontrol agents improved soilborne disease control. Reduced rates of methyl bromide, metam sodium, and 1, 3-dichloropropene, all applied in combination with chloropicrin, were effective in decreasing soil populations of Pythium and Fusarium as well as the presence of Pythium in root debris from the previous crop. The roots of Douglas-fir ( Pseudotsuga menziesii ) seedlings transplanted into each fumigant treatment were also colonized less by Pythium and Fusarium than those transplanted into nonfumigated control plots. However, biocontrol treatments were not effective against either pathogen. Weed biomass and weeding times were also significantly reduced by fumigation. Application costs were similar for all three fumigant treatments, but seedling size was largest from the methyl bromide and metam sodium treatments followed by the 1, 3-dichloropropene treatment. Based on the results of this study, reduced rates of methyl bromide, metam sodium, and 1, 3-dichloropropene show promise in managing soilborne diseases and weeds in forest nurseries. Highlights: Reduced rates of soil fumigants controlled soilborne pathogens and weeds. Combinations of biocontrol agents were ineffective at controlling soilborne pathogens. Nonfumigated soils experience nearly 50% seedling yield loss compared to fumigated soils.